The role of Christian religious beliefs on students' attitudes and reasoning towards Biotechnology issues in Victorian Christian schools - Pope, Timothy Craig (Curtin University, 2014)
The role of religious belief in students’ attitudes and informal reasoning about socioscientific issues in biotechnology was investigated through the analysis of questionnaire and interview data from 177 years 11 and 12 students attending three Australian faith-based schools. It was shown that a Christian worldview was associated with negative attitudes about biotechnology and decreased use of rational and emotive reasoning. Ethical arguments were identified and the frequency that students incorporated faith-based arguments in their decision-making.